Factors influencing consumers' preference on choosing hybrids cars : a case study of greater Tampin OTO Sdn.Bhd (GTO Honda Tampin) / Nurjannah Arbaen - Arbaen, Nurjannah (2018)
The intent of this study is arbitrate the factors influencing consumers' preference in choosing hybrid cars from Honda. The study will appraise the precise relationship between eight criteria which is brand, price, knowledge, efficiency, oil price changes, environmental awareness and maintenance cost with consumers' preference to purchase a hybrid car from Honda. A survey of 80 respondents has been conducted at Greater Tampin Oto Sdn.Bhd, Honda authorized dealer showroom that located at No 3, Jalan Meranti Lestari, Taman Meranti Lestari, Kota, Negeri Sembilan. Simple regression, descriptive analysis and pearson correlation has been used to test the hypotheses developed and research questions. By having a better understanding of the consumers preference to purchase a hybrid car, the automobile industry especially Honda Company can make better marketing approach and allocation of budget in order to attract consumer to purchase a hybrid cars. The finding indicate that among the eight independent variables, only brand and self-image are significant towards the dependent variable. As such, between the two significant variables, brands indicates to be having the highest relationship and contribute as the highest factor influencing consumers' preference in choosing a hybrid car.